Founders’ competentes and start-up performance: an empirical analysis - Pinelli, Michele; Cappa, Francesco; Franco, Stefano; Peruffo, Enzo (Piccola Impresa / Small Business, 2018)
Start-up highly stimulate employment and financial resources, that play a key role for firm’s success, are allocated depending on expected performance. Several studies focus the attention of the relationship between the contingency factors and firm’s performance. However, there is still a lack of studies regarding the link between firm’s expected performance and founder’s features. This research aiming at fill this gap by empirically analyse a sample of 1690 start-up. Findings show that at firm’s early life cycle, founders’ skills have a significant and positive effect on expected performance and on firm’s ability to get funds.